Three-Dimensional Location-Based O&M Data Management System for Large Commercial Office Buildings - Yoon, Jong Han; Cha, Hee Sung; Kim, Jinyoung (Journal of Performance of Constructed Facilities, 2019)
Owing to long building life cycles, facility management (FM) entails a significant responsibility. Furthermore, it is difficult to effectively manage the numerous operation and maintenance (O&M) data generated during the building life cycle, especially for large commercial office buildings. Without this, the facility managers in the operational role cannot achieve a high performance of buildings. However, relatively little research has been conducted on systematic O&M data management processes or methodologies. As a fundamental approach to O&M data management, considerable attention has been given to the analysis on their patterns and trends, specifically based on locational space. The building information modeling (BIM) is a relevant solution for O&M data management that can easily handle data based on locational space. The objective of this study is to develop a practical O&M data management system that employs location-based data analysis. This study has established a data-processing methodology and developed a computerized system using BIM technology. The system allows more accurate cost management and customized O&M work planning and execution, supporting timely decisions for building renovation. As a pioneering work, this study contributes to O&M data management research by establishing an O&M data hierarchy for location-based analysis and by presenting the system's algorithm and framework. Additionally, the result of this research - a location-based O&M data management system (i.e., LOMDS) - facilitates more accurate and effective O&M data analysis, thereby helping optimize O&M decision making for large commercial office buildings.
Keywords: Building Information Model - BIM; Commercial building; Computerized systems; Data management system; Facility management; Operation and maintenance; Performance of buildings; Three dimensional locations; Building information modeling; Commercial buildings; Computer programming; Facility management; Operation and maintenance